Inactivation of aerosolized SARS‐CoV‐2 by 254 nm UV‐C irradiation. (21st September 2022) - Ruetalo, Natalia; Berger, Simon; Niessner, Jennifer; Schindler, Michael
Abstract: Surface residing SARS‐CoV‐2 is efficiently inactivated by UV‐C irradiation. This raises the question whether UV‐C‐based technologies are also suitable to decontaminate SARS‐CoV‐2‐ containing aerosols and which doses are needed to achieve inactivation. Here, we designed a test bench to generate aerosolized SARS‐CoV‐2 and exposed the aerosols to a defined UV‐C dose. Our results demonstrate that the exposure of aerosolized SARS‐CoV‐2 with a low average dose in the order of 0.42–0.51 mJ/cm 2 UV‐C at 254 nm resulted in more than 99.9% reduction in viral titers. Altogether, UV‐C‐based decontamination of aerosols seems highly effective to achieve a significant reduction in SARS‐CoV‐2 infectivity.